Properties of cement made from agricultural waste - Fardad Golbabaei (تحقیقات علوم چوب و کاغذ ایران, 2015)
The main purpose of the production of cement or wood products, composite panels by binding mineral particles mixed with organic materials such as wood and mineral lignocellolosic connectors such as cement, plaster, etc. This study was conducted with the objective of investigating the feasibility of making wood-cement using Poplar sawdust and Portland cement. A total of 30 bricks were made in the laboratories of Wood and production based on ratios of sawdust to cement (5-95, 10-90, 15-85, 25 -75 persent). Mass and volume of samples were measured and then density of bricks was calculated. The composites were tested for compressive strength using testing machine. The mean compressive strength values were 1.75 and 0.38 MPa composites with sawdust to cement ratios of 5-95 and 25-75 respectively, soaked composites swelled irrespective of the sawdust to cement ratio. The compressive strength for the soaked bricks was approximately 40% of the dry weight strength. The composite bricks were found to be unfit for paving and medium heavy load wall construction. Due to their light weight, by imparting decorative mosaics they can be used for interior wall paneling and decoration, where minimal wetting is experienced